Management of Eclampsia by MGSO4 Loading Dose vs Standard Regimen: A Comparative Clinical Trial - Aral , Sarwat; Begum, Rokeya; Nessa, Kamrun; Begum, Shahana (Journal of Chittagong Medical College Teachers’ Association, 2015)
Eclampsia is a life threatening obstretic emergency, the second leading cause of maternal death in Bangladesh. The high maternal morbidity and mortality in Eclampsia is related to multiple or recurrent seizures mostly. Magnesium Sulphate (MgSO4) is the gold standard drug to control and prevent recurrent fits. To compare the occurrence of recurrent seizures with loading dose and standard regimen of MgSO4 (Loading plus maintenance dose). This prospective comparative study was carried out in Department of Obstetrics & Gynaecology of Chittagong Medical College Hospital (CMCH) from January 2011 to December 2011.It was a comparative clinical trial. Study subjects were selected who had eclampsia regarding age, parity, gravidity and gestational age or after recent delivery. Then subjects were categorized into two in alternating method, i.e if first patient was in Group A then next patient was in Group B. Patients who had already received MgSO4 from outside,convulsion due to other causes and having contraindication of MgSO4 therapy were excluded from this study. With written informed consent, Group A received loading dose of inj. MgSO4 and Group B was treated with loading dose plus maintenance dose (standard regimen). The primary outcome was to measure the number of recurrent seizures among the both groups. Secondary outcomes were the side effects, toxicity, Intensive Care Unit (ICU) support, regain of consciousness, normalization of blood pressure and protenuria. The test statistics used to analyze the data were Chi Square test (x2) and unpaired student's t-test. P values of < 0.05 were considered statistically significant The rate of recurrent seizure was 13.3% in loading dose vs 6.3% in standard regimen Group A (0<0.05, RR 2.207, 95% CI 1.089-4.470). Side effects of MgSO4 were higher in Group B (71.1% vs 93%, P<0.01). Considering toxicity 3% was found in loading dose vs 3.8% in standard regimen of MgSO4 i.e almost same (P>0.05). Women who received the standard regimen of MgSO4 are less likely to develop recurrent seizures than those who received loading dose only. Toxicities of MgSO4 are almost same and very little in both the regimen. JCMCTA 2015 ; 26 (1) : 35-40